2007
DOI: 10.1108/00346650710774613
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient composition of foods provided by school canteens in Bahrain

Abstract: PurposeThe aim of this study is to determine the nutritional profile of foods provided by the governmental school canteens in Bahrain.Design/methodology/approachNine types of foods commonly provided in 45 schools in Bahrain were analyzed for their proximate, mineral and heavy metal composition. Proximate composition was determined by measuring the moisture, ash, fat, protein (N × 6.25), crude fiber and carbohydrate content. Minerals and heavy metals were measured using flame or atomic absorption spectroscopy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 38 publications
2
9
1
Order By: Relevance
“…The water content is essentially a measure of the stability of food under storage. The moisture content of grilled beef burger was higher than the data recorded by Musaiger et al (2007) and lower than those reported by Jack (2011). Nearly similar findings were obtained by Prayson et al (2008a) and Al-Amiri et al (2009).…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…The water content is essentially a measure of the stability of food under storage. The moisture content of grilled beef burger was higher than the data recorded by Musaiger et al (2007) and lower than those reported by Jack (2011). Nearly similar findings were obtained by Prayson et al (2008a) and Al-Amiri et al (2009).…”
Section: Discussioncontrasting
confidence: 70%
“…and Musaiger et al (2007). The low moisture content and water activity in food assures a good microbiological stability under storage conditions (Hurtado et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in Qatar the government found that the main source of salt in the Qatari diet was from bread and other baked products [21]. Furthermore, data from food composition tables in the Middle East demonstrated high sodium content in the diet of Middle Easterners, due to the high use of table salt, spices, and pickles [34,35,36]. Therefore, nutritional education focusing on the healthy preparation of food at home, using less salt and fat while cooking, and limiting consumption of high salt foods is recommended.…”
Section: Discussionmentioning
confidence: 99%
“…All data of each food intakes were converted to times per day, and then the portion size of each food items per day was calculated. The daily intakes of energy, macronutrients, and NSPs were estimated for each food items using the food composition tables for Arab Gulf citizens ( 23 ).…”
Section: Methodsmentioning
confidence: 99%